Extreme lymphocytosis with myelomonocytic morphology in a horse with diffuse large B‐cell lymphoma. (21st December 2016) - Meichner, Kristina; Kraszeski, Blaire H.; Durrant, Jessica R.; Grindem, Carol B.; Breuhaus, Babetta A.; Moore, Peter F.; Neel, Jennifer A.; Linder, Keith E.; Borst, Luke B.; Fogle, Jonathan E.; Tarigo, Jaime L.
Abstract: An 11‐year‐old, 443‐kg Haflinger mare was presented to the North Carolina State University Veterinary Teaching Hospital with a 2‐week history of lethargy and a 3‐day duration of anorexia, pyrexia, tachycardia, and ventral edema. Severe pitting edema, peripheral lymphadenopathy, and a caudal abdominal mass were noted on physical examination. An extreme leukocytosis (154.3 × 10 3 /μL) and microscopic hematologic findings suggestive of myelomonocytic leukemia were observed. Serum protein electrophoresis revealed a monoclonal gammopathy and urine protein electrophoresis revealed a monoclonal light chain proteinuria. Necropsy and histopathology confirmed widespread neoplastic infiltration in many organs with a heterogenous population of cells; there was no apparent evidence of bone marrow involvement. Immunohistochemistry confirmed presence of a majority of B cells with a limited antigen expression, admixed with a lower number of T cells. Molecular clonality analysis of IgH2, IgH3, and kappa‐deleting element (KDE, B cell) on whole blood and KDE on infiltrated tissues revealed clonal rearrangements, and the KDE intron clones that amplified in blood and in infiltrated tissue were identical. In contrast, the clonality analysis of T‐cell receptor γ revealed no clonality on blood cells and infiltrated tissues. In conjunction with the histopathologic changes, the lesion was interpreted to be composed of neoplastic B cells with a reactive T‐cell population. Polymerase chain reaction testing for equine herpes virus 5 was negative. The final diagnosis was diffuse large B‐cell lymphoma with a marked hematogenous component.